Retrieval Of Environmental Parameters Over Water Areas Using MODIS Data - Amin, Abd Rahman Mat (2012)
In this study, new and simple algorithms to retrieve cirrus cloud, sediment and aerosol optical depth (AOD) from Moderate Resolution Radiospectrometer (MODIS) imagery is suggested and demonstrated. Techniques used in this thesis are totally new and never been used before by others researchers. The presences of cirrus cloud have been detected utilizing gradient technique algorithm. The algorithm is based on the gradient connecting the 1.38 and 1.24 μm lines of the log– log graph of apparent reflectance against the MODIS wavelength. This algorithm has been tested over the Yellow Sea, Gulf of Martaban, Mediterranean Sea and Atlantic Ocean. The result of this algorithm is then compared with the band ratio technique and the accuracy was determined with percentage difference below 10%. The presence of sediment reflectance in the MODIS imagery not only saturate the ocean color channels, but also enhance the reflectance of near infrared channels used in the atmospheric correction algorithm. This leads to the overestimation of the aerosol contributions and underestimation of the derived water-leaving reflectance in the visible channels. In this study, a new and simple method to detect and mask the presence of sediment reflectance in the MODIS imagery is proposed. The algorithm is based on the difference of the gradient of the line connecting the 0.47 and 2.13 μm channels and 0.47 and 0.66 μm channels of a log–log graph of the apparent reflectance values against their MODIS wavelengths. A sample results over Yellow Sea, Gulf of Martaban and Arabian Sea was demonstrated. The accuracy of the algorithm was tested and determined.